Making the Loyalist Bargain: Surrender, Amnesty and Impunity in Kenya's Decolonization, 1952–63. Issue 1 (1st January 2017) - Anderson, David M.
ABSTRACT: In fighting Mau Mau rebels in Kenya between 1952 and 1956, the British armed and deployed an African militia, known as the Kikuyu Home Guard. This article considers the role played by these allies in the counter-insurgency war, looking specifically at amnesty and surrenders. The British held secret talks with Mau Mau leaders in 1954, and again in 1955, to organize rebel surrenders. The politics of surrenders split the Mau Mau movement, and also raised massive opposition amongst white settlers. Amnesty and impunity were inducements to Mau Mau surrenders, but were offered primarily to prevent disaffection and desertion among loyalist Kikuyu African militia allies who feared prosecution for abuses and atrocities carried out during counter-insurgency operations. Loyalist Africans also feared the consequences of rebels returning to their home communities. Amnesty and promises of impunity thus shaped the character of Kenya's counter-insurgency campaign and the decolonization that followed. This was determined by the need for the British to secure the continued support of African allies up to Kenya's independence in 1963, and beyond.